High-toughness corrosion-resistant aluminum-magnesium composite board as well as preparation method and application thereof
Through the reasonable design of the alloy ingredients in aluminum-magnesium composite materials and the use of asynchronous rolling process, the problem of insufficient intensity and crispy and hard second phase generation of interface combination, and realized high-strength, toughness and corrosion-resistant aluminum-magnesium composite plates Essence
Patent Information
- Application Number
- CN202411489785.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing aluminum-magnesium composite materials have insufficient interfacial bonding strength and are prone to generate a brittle and hard second phase during processing, and it is difficult to take into account multiple performance requirements such as strength, toughness, corrosion resistance and formability.
Through reasonable alloy component design and processing technology, including adding specific elements such as cymbal, copper, calcium, and tin to the aluminum alloy layer and magnesium alloy layer, refine the grain, improve the high temperature stability, and reduce the interface response activity. And use asynchronous rolling processes to introduce shear strain to promote metallurgy binding.
It significantly improves the metallurgical binding performance between aluminum magnesium layers, improves the mechanical properties and corrosion resistance of materials, and forms a high -intensity, toughness, and good formability of high -strong corrosion -resistant aluminum -magnesium composite plates with high strength, toughness and good formability.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal composite materials, and in particular to a high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate material, and a preparation method and application thereof. Background Art
[0002] Aluminum alloys and magnesium alloys are widely used in aerospace, automobile manufacturing, marine engineering and other fields due to their excellent lightweight properties, high specific strength and corrosion resistance. In particular, although the absolute strength of magnesium alloys is usually not as good as that of aluminum alloys, their specific strength (i.e. the ratio of strength to weight) is higher, making them ideal materials for high-performance applications that require weight reduction. However, in certain complex use environments, it is difficult for a single aluminum alloy or magnesium alloy material to simultaneously meet multiple performance requirements such as strength, toughness, corrosion resistance and formability.
[0003] In order to solve these performance deficiencies, aluminum-magnesium composite materials have gradually become a hot spot for research and application. By combining aluminum and magnesium, it is expected that the corrosion resistance of aluminum alloys and the high specific strength of magnesium alloys can be exerted at the same time. However, the traditional aluminum-magnesium composite sheet manufacturing method (such as mechanical lamination, fusion process, etc.) has significant deficiencies in interface bonding. In particular, during the processing, a brittle and hard second phase (such as Mg-Al intermetallic compound) is easily generated at the interface between aluminum and magnesium, which will cause the interface bonding strength to decrease and reduce the toughness and formability of the composite material. In addition, the physical and chemical properties of aluminum and magnesium are quite different, making it difficult for them to achieve good metallurgical bonding under high temperature treatment. Although the prior art CN109702012, CN109433822, and CN110181227 attempt to reduce the generation of brittle and hard second phases and improve the bonding strength of the interface by adding specific alloying elements, adjusting the aluminum-magnesium interface structure, and optimizing the rolling process parameters, it still faces technical challenges and is difficult to simultaneously take into account the multiple performance requirements of the composite material such as strength, toughness, corrosion resistance and formability.
[0004] Therefore, developing an aluminum-magnesium alloy composite plate that can effectively reduce the formation of brittle and hard second phases at the aluminum-magnesium interface and improve the metallurgical bonding strength of the two while having good comprehensive performance remains a technical challenge in the current materials field. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength, tough and corrosion-resistant aluminum-magnesium composite plate and its preparation method and application, so as to solve the problems of insufficient interface bonding strength of existing aluminum-magnesium composite materials and easy generation of brittle and hard second phases during processing. Through reasonable alloy composition design and processing technology, the present invention significantly improves the metallurgical bonding performance between aluminum-magnesium layers, improves the mechanical properties and corrosion resistance of the material, and the obtained high-strength, tough and corrosion-resistant aluminum-magnesium composite plate is suitable for fields such as aerospace, automobile manufacturing, and marine engineering that require lightweight, high-strength and high-corrosion-resistant materials.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate, wherein the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate comprises a first aluminum alloy layer, a magnesium alloy layer, and a second aluminum alloy layer stacked in sequence;
[0008] The first aluminum alloy layer and the second aluminum alloy layer independently contain the following components in mass fraction: Mg 3.0-5.5%, Mn 0.3-1.2%, Si 0.1-0.4%, Fe 0.15-0.4%, Cu 0.05-0.75%, Sc 0.1-0.3%, and Al balance;
[0009] The magnesium alloy layer contains the following components in mass fractions: Al 2.0-4.0%, Ca 1.5-4.0%, Mn 0.2-1.0%, Be 0.1-0.5%, Sn 0.5-2.0%, and Mg balance.
[0010] The present invention also provides a method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate, comprising the following steps:
[0011] (1) mixing the components contained in the first aluminum alloy layer and performing a first smelting to obtain a first aluminum alloy; mixing the components contained in the second aluminum alloy layer and performing a second smelting to obtain a second aluminum alloy; and mixing the components contained in the magnesium alloy layer under a protective atmosphere and performing a third smelting to obtain a magnesium alloy;
[0012] (2) subjecting the first aluminum alloy to a first solid solution treatment to obtain a first aluminum alloy layer; subjecting the second aluminum alloy to a second solid solution treatment to obtain a second aluminum alloy layer; and subjecting the magnesium alloy to a third solid solution treatment to obtain a magnesium alloy layer;
[0013] (3) stacking the first aluminum alloy layer, the magnesium alloy layer, and the second aluminum alloy layer in order, and then rolling and heat treating them in sequence after the stacking is completed to obtain the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate.
[0014] Preferably, in step (1), the temperatures of the first smelting and the second smelting are independently 700-770°C, and the temperature of the third smelting is 680-750°C.
[0015] Preferably, in step (2), the temperature of the first solution treatment and the second solution treatment are independently 500 to 550° C., and the time of the first solution treatment and the second solution treatment are independently 2 to 12 hours;
[0016] The temperature of the third solution treatment is 450-500° C., and the time of the third solution treatment is 4-24 hours.
[0017] Preferably, in step (3), the thickness of the first aluminum alloy layer and the second aluminum alloy layer are independently 4 to 8 mm, and the thickness of the magnesium alloy layer is 6 to 10 mm.
[0018] Preferably, the number of rolling passes in step (3) is ≥ 2 times; the total rolling reduction rate is 50-85%;
[0019] The rolling reduction rate of the first pass is 50-75%, and the rolling temperature of the first pass is 400-480°C; the rolling reduction rates of the remaining passes are independently 10-15%, and the rolling temperatures of the remaining passes are independently 400-490°C; the rolling temperatures of the remaining passes are ≥ the rolling temperature of the first pass.
[0020] Preferably, in step (3), the rotation speed of the upper rolling roller is 5 to 10 m / min, the rotation speed of the lower rolling roller is 3 to 8 m / min, and the asynchronous ratio of rolling is 1.2 to 1.6.
[0021] Preferably, the heat treatment temperature in step (3) is 200-300° C., and the heat treatment time is 0.5-2 h.
[0022] The present invention also provides the application of the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate in aerospace, automobile manufacturing or marine engineering.
[0023] The beneficial effects of the present invention are:
[0024] The invention provides a high-strength, tough and corrosion-resistant aluminum-magnesium composite plate material, comprising a first aluminum alloy layer, a magnesium alloy layer and a second aluminum alloy layer stacked in sequence; the first aluminum alloy layer and the second aluminum alloy layer independently contain the following components by mass fraction: Mg 3.0-5.5%, Mn 0.3-1.2%, Si 0.1-0.4%, Fe0.15-0.4%, Cu 0.05-0.75%, Sc 0.1-0.3%, Al balance; the magnesium alloy layer contains the following components by mass fraction: Al 2.0-4.0%, Ca 1.5-4.0%, Mn 0.2-1.0%, Be 0.1-0.5%, Sn0.5-2.0%, Mg balance. In the aluminum alloy layer, scandium (Sc) effectively inhibits the recrystallization process by refining the grains, slows down the generation of brittle intermetallic compounds at the interface, and significantly improves the bonding strength of the aluminum-magnesium interface. The high temperature stability of scandium ensures that the interface can be evenly bonded during rolling and heat treatment, reducing interface failure caused by stress concentration. The addition of copper (Cu) enhances the stability of the bonding zone through solid solution strengthening and interface interdiffusion, reduces the formation of brittle phases, and makes the interface reaction more uniform and controllable. Manganese (Mn) further inhibits the precipitation of unfavorable brittle phases at the interface by forming stable Al6Mn compounds, improving overall corrosion resistance and durability. In the magnesium alloy layer, calcium (Ca) reduces the excessive reaction at the interface between magnesium and aluminum by reducing the activity of the interface reaction, inhibits the formation of brittle phases, and significantly improves the stability of the bonding interface. The addition of beryllium (Be) improves the oxidation resistance and heat stability of magnesium alloys, effectively reduces the formation of oxides during high temperature processing, and further inhibits the formation of poor interface phases. Tin (Sn) improves the plasticity and fluidity of magnesium alloys, making the stress distribution more uniform during rolling, reducing cracks caused by stress concentration, and ensuring the quality and stability of interface bonding.
[0025] In addition, the present invention adopts an asynchronous rolling process, and by adjusting the roller speed difference between the aluminum alloy layer and the magnesium alloy layer, shear strain is generated, which promotes the metallurgical bonding between the aluminum and magnesium layers. The shear strain introduces lateral plastic flow at the interface, increases the deformation coordination at the interface, reduces the relative sliding and stress concentration between the layers, and thus effectively improves the bonding strength of the interface. On the other hand, the large reduction rate of the initial pass is beneficial to the plastic deformation of the magnesium alloy layer, which can more fully change the microstructure of the magnesium alloy and promote it to form a closer bond with the aluminum alloy layer at the interface. Through the high deformation amount during the asynchronous rolling process, the interface reaction is carried out more evenly, thereby reducing the generation of brittle and hard intermetallic compounds (such as Al3Mg2). This interface bonding achieved by plastic flow and strain regulation ensures that the composite material effectively weakens the formation of brittle phases while improving the bonding strength, and improves the toughness and corrosion resistance of the material. The present invention effectively solves the problems of insufficient interface bonding strength and easy generation of brittle and hard second phases in aluminum-magnesium composite materials through precise alloy composition design and optimized rolling process. DETAILED DESCRIPTION
[0026] The present invention provides a high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate, wherein the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate comprises a first aluminum alloy layer, a magnesium alloy layer, and a second aluminum alloy layer stacked in sequence;
[0027] The first aluminum alloy layer and the second aluminum alloy layer independently contain the following components in mass fraction: Mg 3.0-5.5%, Mn 0.3-1.2%, Si 0.1-0.4%, Fe 0.15-0.4%, Cu 0.05-0.75%, Sc 0.1-0.3%, and Al balance;
[0028] The magnesium alloy layer contains the following components in mass fractions: Al 2.0-4.0%, Ca 1.5-4.0%, Mn 0.2-1.0%, Be 0.1-0.5%, Sn 0.5-2.0%, and Mg balance.
[0029] In the present invention, the scandium (Sc) and copper (Cu) elements in the first aluminum alloy layer and the second aluminum alloy layer effectively promote the metallurgical bonding of the aluminum-magnesium layer and improve the bonding strength during the rolling process of the aluminum-magnesium composite plate by refining the grains and improving the high-temperature stability. Scandium (Sc) refines the grains, reduces the concentration of interfacial stress and the formation of brittle intermetallic compounds, and manganese (Mn) inhibits the precipitation of brittle hard phases by forming stable compounds. The reasonable combination of these elements effectively weakens the formation of brittle hard phases, ensuring that the composite plate has excellent mechanical properties and corrosion resistance.
[0030] In the present invention, in the magnesium alloy layer, calcium (Ca) reduces the generation of brittle phase by reducing the interfacial reaction activity, beryllium (Be) improves the oxidation resistance of the magnesium alloy and stabilizes the interface bonding, and tin (Sn) reduces stress concentration by improving plasticity, improves the plastic forming performance of the magnesium alloy, and inhibits the generation of brittle hard phase at the interface. The reasonable combination of these elements ensures that the composite plate has high bonding strength and good mechanical properties.
[0031] In the present invention, preferably, the first aluminum alloy layer and the second aluminum alloy layer independently contain the following components in mass fraction: Mg 3.5-5.0%, Mn 0.5-1.0%, Si 0.15-0.35%, Fe 0.2-0.35%, Cu 0.10-0.65%, Sc 0.15-0.25%, and Al balance.
[0032] In the present invention, further preferably, the first aluminum alloy layer and the second aluminum alloy layer independently contain the following components in mass fraction: Mg 4.0-4.5%, Mn 0.6-0.9%, Si 0.2-0.3%, Fe0.25-0.3%, Cu 0.20-0.55%, Sc 0.17-0.23%, and Al balance.
[0033] In the present invention, more preferably, the first aluminum alloy layer and the second aluminum alloy layer independently contain the following components in mass fraction: Mg 4.2-4.3%, Mn 0.7-0.8%, Si 0.25%, Fe 0.26-0.28%, Cu 0.30-0.40%, Sc 0.2%, and Al balance.
[0034] In the present invention, preferably, the magnesium alloy layer comprises the following components in mass fractions: Al 2.5-3.5%, Ca 2.0-3.5%, Mn 0.4-0.8%, Be 0.2-0.4%, Sn 0.7-1.8%, and Mg as the balance.
[0035] In the present invention, further preferably, the magnesium alloy layer comprises the following components in mass fractions: Al 2.7-3.3%, Ca 2.5-3.0%, Mn 0.5-0.7%, Be 0.25-0.35%, Sn 1-1.5%, and Mg as the balance.
[0036] In the present invention, more preferably, the magnesium alloy layer comprises the following components in mass fractions: Al 3.0%, Ca 2.6-2.8%, Mn 0.6%, Be 0.3%, Sn 1.2-1.3%, and Mg as the balance.
[0037] The present invention also provides a method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate, comprising the following steps:
[0038] (1) mixing the components contained in the first aluminum alloy layer and performing a first smelting to obtain a first aluminum alloy; mixing the components contained in the second aluminum alloy layer and performing a second smelting to obtain a second aluminum alloy; and mixing the components contained in the magnesium alloy layer under a protective atmosphere and performing a third smelting to obtain a magnesium alloy;
[0039] (2) subjecting the first aluminum alloy to a first solid solution treatment to obtain a first aluminum alloy layer; subjecting the second aluminum alloy to a second solid solution treatment to obtain a second aluminum alloy layer; and subjecting the magnesium alloy to a third solid solution treatment to obtain a magnesium alloy layer;
[0040] (3) stacking the first aluminum alloy layer, the magnesium alloy layer, and the second aluminum alloy layer in order, and then rolling and heat treating them in sequence after the stacking is completed to obtain the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate.
[0041] In the present invention, in step (1), the components contained in the first aluminum alloy layer are mixed and the process of first smelting is preferably as follows: first, pure metal Al is added, and after Al is completely melted, Mg, Cu, Mn, Si and Sc are added, wherein Mg is added in the form of pure metal Mg or Al-Mg alloy, Cu is added in the form of pure metal Cu or Al-Cu alloy, Mn is added in the form of Al-Mn alloy, Si is added in the form of Al-Si alloy, and Sc is added in the form of Al-Sc alloy; after all raw materials are melted, the first smelting is completed; sufficient stirring is maintained during the addition and the first smelting process to ensure the uniformity of the alloy components; the order and amount of addition of each raw material are determined by a technician in this field according to the components contained in the first aluminum alloy through conventional selection; after the first smelting is completed, pouring is performed and naturally cooled to room temperature to obtain the first aluminum alloy; wherein the source of Fe in the final first aluminum alloy is pure metal Al and Al in the intermediate alloy.
[0042] In the present invention, in step (1), the preparation process of the second aluminum alloy is the same as that of the first aluminum alloy.
[0043] In the present invention, in step (1), the protective atmosphere is preferably a mixed atmosphere of CO2 and SF6 or an argon atmosphere; the volume ratio of CO2 and SF6 in the mixed atmosphere of CO2 and SF6 is preferably 95-105:1, further preferably 97-103:1, and more preferably 100:1; the purpose of setting the protective atmosphere is to prevent oxidation and combustion of the magnesium melt during the smelting process; the process of mixing the components contained in the magnesium alloy layer and performing the third smelting is preferably: first, adding pure metal Mg, and after Mg is completely melted, adding pure metal Al, Al-Ca alloy, A l-Mn alloy, Al-Be alloy and pure metal Sn, after all raw materials are melted, complete the third smelting; keep sufficient stirring during the feeding and the third smelting process to ensure the uniformity of the alloy composition; the order and amount of adding each raw material are determined by technicians in this field through conventional selection according to the components contained in the magnesium alloy; after the third smelting is completed, pouring is carried out and naturally cooled to room temperature to obtain the magnesium alloy; wherein, the Al content is low in the process of preparing the magnesium alloy, and correspondingly, the amount of aluminum raw material added is low, so the Fe content in the final magnesium alloy can be ignored.
[0044] In the present invention, the temperatures of the first smelting and the second smelting in step (1) are independently preferably 700-770°C, more preferably 710-740°C, and more preferably 720-730°C; the temperature of the third smelting is preferably 680-750°C, more preferably 690-720°C, and more preferably 700-710°C.
[0045] In the present invention, the temperatures of the first solution treatment and the second solution treatment in step (2) are independently preferably 500-550°C, further preferably 510-540°C, and more preferably 520-530°C; the times of the first solution treatment and the second solution treatment are independently preferably 2-12h, further preferably 4-10h, and more preferably 6-8h.
[0046] In the present invention, the temperature of the third solution treatment is preferably 450-500°C, more preferably 460-490°C, and more preferably 470-480°C; the time of the third solution treatment is preferably 4-24h, more preferably 10-20h, and more preferably 12-16h.
[0047] In the present invention, the purpose of the first solid solution treatment and the second solid solution treatment in step (2) is to improve the plasticity and corrosion resistance of the alloy and enhance the forming performance of subsequent rolling; the purpose of the third solid solution treatment is to refine the grains and enhance the corrosion resistance and strength of the magnesium alloy; after step (2) is completed, the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are independently cleaned, dried after cleaning, and then step (3) is performed.
[0048] In the present invention, cleaning is performed by conventional technical means in the art, and the cleaning method preferably includes mechanical grinding, chemical cleaning and water washing performed in sequence. When the cleaning object is the first aluminum alloy layer or the second aluminum alloy layer, the chemical cleaning reagent is independently preferably a mixed solution of phosphoric acid and nitric acid, a hydrofluoric acid solution or a sodium hydroxide solution; when the cleaning object is a magnesium alloy layer, the chemical cleaning reagent is preferably a mixed solution of chromic acid and nitric acid, a hydrofluoric acid solution, a trisodium phosphate solution or a sodium carbonate solution; the mass fraction of each reagent is determined by conventional technical means in the art; the purpose of cleaning is to remove the oxide layer and impurities, ensure the cleanliness of the alloy layer bonding surface, and improve the bonding effect in the subsequent rolling process.
[0049] In the present invention, the thickness of the first aluminum alloy layer and the second aluminum alloy layer in step (3) is preferably 4 to 8 mm, more preferably 5 to 7 mm, and more preferably 6 mm; the thickness of the magnesium alloy layer is preferably 6 to 10 mm, more preferably 7 to 9 mm, and more preferably 8 mm.
[0050] In the present invention, in step (3), during lamination, the transverse lengths of the first aluminum alloy layer and the second aluminum alloy layer used are preferably greater than the transverse length of the magnesium alloy layer used, so as to achieve a better bite effect in the subsequent rolling process.
[0051] In the present invention, the number of rolling passes in step (3) is preferably ≥2 times, further preferably ≥3 times, and more preferably ≥4 times; the total rolling reduction rate (the reduction rate is calculated by subtracting the thickness of the composite plate after rolling from the thickness of the initial composite plate divided by the thickness of the initial composite plate) is preferably 50-85%, further preferably 65-80%, and more preferably 70-75%.
[0052] In the present invention, the first pass is large strain rolling, and the rolling reduction rate of the first pass is preferably 50-75%, more preferably 55-70%, and more preferably 60-65%; the rolling temperature of the first pass is preferably 400-480°C, more preferably 420-460°C, and more preferably 430-450°C; the rolling reduction rates of the remaining passes are independently preferably 10-15%, more preferably 11-14%, and more preferably 12-13%; the rolling temperatures of the remaining passes are independently preferably 400-490°C, more preferably 420-470°C, and more preferably 430-460°C; the rolling temperatures of the remaining passes are preferably ≥ the rolling temperature of the first pass.
[0053] In the present invention, the large reduction rate in the first pass is beneficial to the plastic deformation of the middle magnesium alloy layer which is difficult to deform, and can promote the interface bonding during the plastic deformation process; through the specific rolling process of the present invention, good metallurgical bonding can be ensured and the generation of brittle phases can be reduced.
[0054] In the present invention, the rotation speed of the upper rolling roller in step (3) is preferably 5-10 m / min, more preferably 6-9 m / min, and more preferably 7-8 m / min; the rotation speed of the lower rolling roller is preferably 3-8 m / min, more preferably 4-7 m / min, and more preferably 5-6 m / min; the asynchronous ratio of rolling is preferably 1.2-1.9, more preferably 1.3-1.8, and more preferably 1.6-1.75; the rolling in step (3) adopts an asynchronous rolling process, and the rotation speeds of the upper and lower rolling rollers are different, so that the shear strain between the aluminum-magnesium layers is increased, the metallurgical bonding of the two layers of materials is promoted, the plastic deformation resistance of the magnesium alloy layer is reduced, and the forming ability of the magnesium alloy layer is improved.
[0055] In the present invention, the temperature of the heat treatment in step (3) is preferably 200-300°C, more preferably 230-280°C, and more preferably 250-260°C; the time of the heat treatment is preferably 0.5-2h, more preferably 1-1.5h, and more preferably 1.2-1.3h; the purpose of the heat treatment is to reduce the residual stress generated during the rolling process and optimize the interface metallurgical bonding strength, corrosion resistance and mechanical properties of the composite material.
[0056] The present invention also provides the application of the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate in aerospace, automobile manufacturing or marine engineering.
[0057] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0058] Example 1
[0059] In this embodiment, the first aluminum alloy layer contains the following components in mass fraction: Mg 4.0%, Mn 0.6%, Si 0.3%, Fe 0.2%, Cu 0.2%, Sc 0.2%, and Al balance; the second aluminum alloy layer has the same composition as the first aluminum alloy layer; the magnesium alloy layer contains the following components in mass fraction: Al 3.0%, Ca 3.0%, Mn 0.5%, Be 0.3%, Sn 1.5%, and Mg balance.
[0060] The components contained in the first aluminum alloy layer are mixed and first smelting is performed. Specifically, first, pure metal Al is added. After Al is completely melted, Al-Mg alloy, Al-Cu alloy, Al-Mn alloy, Al-Si alloy and Al-Sc alloy are added in sequence (there is no requirement for the type of each alloy, as long as the requirements for the content of the components in the final aluminum alloy layer are met). After all the raw materials are melted, the first smelting is completed. The temperature of the first smelting is set to 700° C. During the addition and the first smelting process, sufficient stirring is maintained to ensure the uniformity of the alloy components. After the first smelting is completed, pouring is performed and the alloy is naturally cooled to room temperature to obtain the first aluminum alloy (the source of Fe contained in the first aluminum alloy is pure metal Al and the intermediate alloy). ; The second aluminum alloy is prepared by the same preparation method as the first aluminum alloy; in an argon atmosphere, the components contained in the magnesium alloy layer are mixed and a third smelting is performed. Specifically, first, pure metal Mg is added, and after Mg is completely melted, pure metal Al, Al-Ca alloy, Al-Mn alloy, Al-Be alloy and pure metal Sn are added in sequence (there is no requirement for the type of each alloy, as long as the requirements for the content of the components in the final magnesium alloy layer are met), and after all the raw materials are melted, the third smelting is completed; the temperature of the third smelting is set to 700° C., and sufficient stirring is maintained during the addition and the third smelting process to ensure the uniformity of the alloy components. After the third smelting is completed, it is poured and naturally cooled to room temperature to obtain a magnesium alloy;
[0061] The first aluminum alloy layer was prepared by solution treatment at 520°C for 6 hours; the second aluminum alloy layer was prepared by the same preparation method as the first aluminum alloy layer; the magnesium alloy layer was prepared by solution treatment at 480°C for 12 hours to obtain the magnesium alloy layer; the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer were mechanically polished, chemically cleaned and washed with water independently and in sequence, wherein the reagent for chemical cleaning of the first aluminum alloy layer and the second aluminum alloy layer was a hydrofluoric acid solution with a mass fraction of 2%; the reagent for chemical cleaning of the magnesium alloy was a hydrofluoric acid solution with a mass fraction of 0.5%; after washing, the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer were dried, and the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer were prepared by the same preparation method as the first aluminum alloy layer. The laminated sheets were stacked in sequence, wherein the thickness of the first aluminum alloy layer and the second aluminum alloy layer were both 6 mm, the thickness of the magnesium alloy layer was 8 mm, the lateral length of the first aluminum alloy layer and the second aluminum alloy layer was greater than the lateral length of the magnesium alloy layer used, and the laminated sheets were rolled after the laminated sheets were completed, and the rolling conditions were set as follows: 2 passes, a total reduction rate of 69.2%, a rolling reduction rate of 65% in the first pass, a rolling temperature of 450°C in the first pass, a rolling reduction rate of 12% in the remaining passes (i.e., the second pass), and a rolling temperature of 460°C in the remaining passes; the upper roller speed was 8 m / min, the lower roller speed was 5 m / min, the asynchronous ratio was 1.6, and finally heat treated at 250°C for 1 h to obtain a high-strength, tough, and corrosion-resistant aluminum-magnesium composite sheet.
[0062] The high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate prepared in this embodiment was subjected to performance tests (mechanical property tests were based on standard GB / T228.1, and exfoliation corrosion tests were based on standard GB / T22639). The results showed that the tensile strength of the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate in this embodiment was 370 MPa, the yield strength was 340 MPa, and the elongation was 16%; the exfoliation corrosion grade was N.
[0063] Example 2
[0064] In this embodiment, the first aluminum alloy layer contains the following components in mass fraction: Mg 3.5%, Mn 0.5%, Si 0.2%, Fe 0.2%, Cu 0.1%, Sc 0.15%, and Al balance; the second aluminum alloy layer has the same composition as the first aluminum alloy layer; the magnesium alloy layer contains the following components in mass fraction: Al 2.5%, Ca 2.0%, Mn 0.4%, Be 0.2%, Sn 1.2%, and Mg balance.
[0065] The components contained in the first aluminum alloy layer are mixed and first smelting is performed. Specifically, first, pure metal Al is added. After Al is completely melted, Al-Mg alloy, Al-Cu alloy, Al-Mn alloy, Al-Si alloy and Al-Sc alloy are added in sequence (there is no requirement for the type of each alloy, as long as the requirements for the content of the components in the final aluminum alloy layer are met). After all the raw materials are melted, the first smelting is completed. The temperature of the first smelting is set to 700° C. During the addition and the first smelting process, sufficient stirring is maintained to ensure the uniformity of the alloy components. After the first smelting is completed, pouring is performed and the alloy is naturally cooled to room temperature to obtain the first aluminum alloy (the source of Fe contained in the first aluminum alloy is pure metal Al and the intermediate alloy). ; The second aluminum alloy is prepared by the same preparation method as the first aluminum alloy; in an argon atmosphere, the components contained in the magnesium alloy layer are mixed and a third smelting is performed. Specifically, first, pure metal Mg is added, and after Mg is completely melted, pure metal Al, Al-Ca alloy, Al-Mn alloy, Al-Be alloy and pure metal Sn are added in sequence (there is no requirement for the type of each alloy, as long as the requirements for the content of the components in the final magnesium alloy layer are met), and after all the raw materials are melted, the third smelting is completed; the temperature of the third smelting is set to 700° C., and sufficient stirring is maintained during the addition and the third smelting process to ensure the uniformity of the alloy components. After the third smelting is completed, it is poured and naturally cooled to room temperature to obtain a magnesium alloy;
[0066] The first aluminum alloy layer is obtained by subjecting the first aluminum alloy layer to a solid solution treatment at 510°C and setting the solid solution treatment time to 4 hours; the second aluminum alloy layer is prepared by the same preparation method as the first aluminum alloy layer; the magnesium alloy layer is subjected to a solid solution treatment at 460°C and setting the solid solution treatment time to 10 hours to obtain a magnesium alloy layer; the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are independently subjected to mechanical grinding, chemical cleaning and water washing in sequence, wherein the reagent for chemical cleaning of the first aluminum alloy layer and the second aluminum alloy layer is a sodium hydroxide solution with a mass fraction of 8%; the reagent for chemical cleaning of the magnesium alloy is a sodium carbonate solution with a mass fraction of 6%; after the water washing, the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are dried, and then the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are subjected to mechanical grinding, chemical cleaning and water washing in sequence, wherein the reagent for chemical cleaning of the first aluminum alloy layer and the second aluminum alloy layer is a sodium hydroxide solution with a mass fraction of 8%; the reagent for chemical cleaning of the magnesium alloy is a sodium carbonate solution with a mass fraction of 6%; after the water washing, the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are subjected to chemical cleaning in accordance with the method described in the preceding paragraph. The laminated sheets were stacked sequentially, wherein the thickness of the first aluminum alloy layer and the second aluminum alloy layer were both 5 mm, the thickness of the magnesium alloy layer was 7 mm, the lateral length of the first aluminum alloy layer and the second aluminum alloy layer was greater than the lateral length of the magnesium alloy layer used, and the laminated sheets were rolled after the laminated sheets were completed, and the rolling conditions were set as follows: 2 passes, a total reduction rate of 64.8%, a rolling reduction rate of 60% for the first pass, a rolling temperature of 430°C for the first pass, a rolling reduction rate of 12% for the remaining passes (i.e., the second pass), and a rolling temperature of 430°C for the remaining passes; the upper roller speed was 7 m / min, the lower roller speed was 4 m / min, the asynchronous ratio was 1.75, and finally heat treated at 230°C for 1.5 h to obtain a high-strength, tough, and corrosion-resistant aluminum-magnesium composite sheet.
[0067] The same testing method as in Example 1 was used to perform a performance test on the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate prepared in this example. The results showed that the tensile strength of the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate in this example was 360 MPa, the yield strength was 330 MPa, and the elongation was 18%; the exfoliation corrosion grade was N.
[0068] Example 3
[0069] In this embodiment, the first aluminum alloy layer contains the following components in mass fraction: Mg 5.0%, Mn 0.8%, Si 0.4%, Fe 0.3%, Cu 0.4%, Sc 0.25%, and Al balance; the second aluminum alloy layer has the same composition as the first aluminum alloy layer; the magnesium alloy layer contains the following components in mass fraction: Al 4.0%, Ca 3.5%, Mn 0.6%, Be 0.5%, Sn 2.0%, and Mg balance.
[0070] The components contained in the first aluminum alloy layer are mixed and first smelting is performed. Specifically, first, pure metal Al is added. After Al is completely melted, Al-Mg alloy, Al-Cu alloy, Al-Mn alloy, Al-Si alloy and Al-Sc alloy are added in sequence (there is no requirement for the type of each alloy, as long as the requirements for the content of the components in the final aluminum alloy layer are met). After all the raw materials are melted, the first smelting is completed. The temperature of the first smelting is set to 700° C. During the addition and the first smelting process, sufficient stirring is maintained to ensure the uniformity of the alloy components. After the first smelting is completed, pouring is performed and the alloy is naturally cooled to room temperature to obtain the first aluminum alloy (the source of Fe contained in the first aluminum alloy is pure metal Al and the intermediate alloy). ; The second aluminum alloy is prepared by the same preparation method as the first aluminum alloy; in an argon atmosphere, the components contained in the magnesium alloy layer are mixed and a third smelting is performed. Specifically, first, pure metal Mg is added, and after Mg is completely melted, pure metal Al, Al-Ca alloy, Al-Mn alloy, Al-Be alloy and pure metal Sn are added in sequence (there is no requirement for the type of each alloy, as long as the requirements for the content of the components in the final magnesium alloy layer are met), and after all the raw materials are melted, the third smelting is completed; the temperature of the third smelting is set to 700° C., and sufficient stirring is maintained during the addition and the third smelting process to ensure the uniformity of the alloy components. After the third smelting is completed, it is poured and naturally cooled to room temperature to obtain a magnesium alloy;
[0071] The first aluminum alloy layer is obtained by subjecting the first aluminum alloy layer to a solution treatment at 530°C for 8 hours; the second aluminum alloy layer is prepared by the same preparation method as the first aluminum alloy layer; the magnesium alloy layer is subjected to a solution treatment at 490°C for 16 hours to obtain a magnesium alloy layer; the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are independently and sequentially subjected to mechanical polishing, chemical cleaning and water washing, wherein the reagent for chemical cleaning of the first aluminum alloy layer and the second aluminum alloy layer is a mixed solution of phosphoric acid and nitric acid, wherein the mass fraction of phosphoric acid in the mixed solution is 15%, and the mass fraction of nitric acid in the mixed solution is 3%; the reagent for chemical cleaning of the magnesium alloy is a mixed solution of chromic acid and nitric acid, wherein the mass fraction of chromic acid in the mixed solution is 4%, and the mass fraction of nitric acid in the mixed solution is 1.5%; after water washing, the layers are dried After drying, the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are stacked in this order, wherein the thickness of the first aluminum alloy layer and the second aluminum alloy layer are both 7 mm, the thickness of the magnesium alloy layer is 9 mm, and the lateral length of the first aluminum alloy layer and the second aluminum alloy layer is greater than the lateral length of the magnesium alloy layer used. After the stacking is completed, rolling is performed, and the rolling conditions are set as follows: 2 passes, a total reduction rate of 73.9%, a rolling reduction rate of 70% for the first pass, a rolling temperature of 460°C for the first pass, a rolling reduction rate of 13% for the remaining passes (i.e., the second pass), a rolling temperature of 470°C for the remaining passes, an upper roller speed of 10 m / min, a lower roller speed of 6 m / min, an asynchronous ratio of 1.67, and finally a heat treatment at 260°C for 1 h to obtain a high-strength, tough, and corrosion-resistant aluminum-magnesium composite plate.
[0072] The same testing method as in Example 1 was used to perform a performance test on the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate prepared in this example. The results showed that the tensile strength of the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate in this example was 390 MPa, the yield strength was 360 MPa, and the elongation was 14%; the exfoliation corrosion grade was N.
[0073] Comparative Example 1
[0074] In this comparative example, the composition of the first aluminum alloy layer is set according to 5083 aluminum alloy; the composition of the second aluminum alloy layer is the same as that of the first aluminum alloy layer; the magnesium alloy layer contains the following components by mass fraction: Al 3.0%, Ca 2.5%, Mn 0.3%, and Mg balance.
[0075] The components contained in the first aluminum alloy layer are mixed, and a first smelting is performed, and the temperature of the first smelting is set to 710° C. After the first smelting is completed, the first aluminum alloy is cast and naturally cooled to room temperature to obtain a first aluminum alloy; the second aluminum alloy is prepared by the same preparation method as the first aluminum alloy; in an argon atmosphere, the components contained in the magnesium alloy layer are mixed, and a third smelting is performed, and the temperature of the third smelting is set to 700° C. After the third smelting is completed, the magnesium alloy is cast and naturally cooled to room temperature to obtain a magnesium alloy;
[0076] The first aluminum alloy is subjected to a solution treatment at 500°C for 4 hours to obtain a first aluminum alloy layer; the second aluminum alloy layer is prepared by the same preparation method as the first aluminum alloy layer; the magnesium alloy is subjected to a solution treatment at 450°C for 6 hours to obtain a magnesium alloy layer; the first aluminum alloy layer, the magnesium alloy layer and the second aluminum alloy layer are independently and sequentially subjected to mechanical grinding, chemical cleaning and water washing, wherein the reagent for chemical cleaning of the first aluminum alloy layer and the second aluminum alloy layer is a hydrofluoric acid solution with a mass fraction of 2%; the reagent for chemical cleaning of the magnesium alloy is a hydrofluoric acid solution with a mass fraction of 0.5%; After washing, the material is dried and stacked in the order of a first aluminum alloy layer, a magnesium alloy layer and a second aluminum alloy layer, wherein the thickness of the first aluminum alloy layer and the second aluminum alloy layer are both 5 mm, the thickness of the magnesium alloy layer is 7 mm, and the lateral length of the first aluminum alloy layer and the second aluminum alloy layer is greater than the lateral length of the magnesium alloy layer used. After stacking, the material is rolled, and the rolling conditions are set as follows: a single-pass reduction rate of approximately 15%, a total rolling reduction rate of 60%, a rolling temperature of 400°C, an upper roller speed of 5m / min, and a lower roller speed of 5m / min. Finally, the material is heat treated at 200°C for 1h to obtain a composite plate.
[0077] The same testing method as in Example 1 was used to test the performance of the composite plate prepared in this comparative example, and the results showed that the tensile strength of the composite plate in this comparative example was 240 MPa, the yield strength was 200 MPa, and the elongation was 8%; the exfoliation corrosion grade was PB.
[0078] It can be seen from the above embodiments and comparative examples that the tensile strength of the high-strength, tough, and corrosion-resistant aluminum-magnesium composite sheet prepared in embodiments 1 to 3 is between 360 and 390 MPa, and the yield strength is between 330 and 360 MPa, which are significantly higher than 240 MPa and 200 MPa of the comparative example. The elongation of the high-strength, tough, and corrosion-resistant aluminum-magnesium composite sheet prepared in embodiments 1 to 3 is between 14 and 18%, which is better than 8% of the comparative example. This shows that the present invention has greatly improved the mechanical properties of the composite sheet by optimizing the alloy composition design and adopting the asynchronous rolling process.
[0079] According to the exfoliation corrosion test standard GB / T22639, the exfoliation corrosion grade of the high-toughness and corrosion-resistant aluminum-magnesium composite plates prepared in Examples 1 to 3 is N grade, indicating that they have excellent corrosion resistance. The exfoliation corrosion grade of Comparative Example 1 is PB grade, indicating that its corrosion performance is poor.
[0080] It can be seen that the high-strength, tough and corrosion-resistant aluminum-magnesium composite plates prepared in Examples 1 to 3 are significantly superior to the composite plates prepared in Comparative Example 1 in terms of mechanical properties and corrosion resistance. This is mainly attributed to the addition of elements such as scandium (Sc) and copper (Cu) in the aluminum alloy component and calcium (Ca), tin (Sn) and beryllium (Be) in the magnesium alloy component. These elements improve the overall performance of the composite material by refining the grains and improving the high-temperature stability and corrosion resistance of the alloy. At the same time, the asynchronous rolling process introduces shear strain between the aluminum alloy and magnesium alloy layers, enhances the interface bonding strength, effectively reduces the formation of brittle intermetallic compounds, and improves the comprehensive performance of the material.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-strength, tough and corrosion-resistant aluminum-magnesium composite plate, characterized in that: The high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate comprises a first aluminum alloy layer, a magnesium alloy layer and a second aluminum alloy layer stacked in sequence; The first aluminum alloy layer and the second aluminum alloy layer independently contain the following components in mass fraction: Mg 3.0-5.5%, Mn 0.3-1.2%, Si 0.1-0.4%, Fe 0.15-0.4%, Cu 0.05-0.75%, Sc 0.1-0.3%, and Al balance; The magnesium alloy layer contains the following components in mass fractions: Al 2.0-4.0%, Ca 1.5-4.0%, Mn 0.2-1.0%, Be 0.1-0.5%, Sn 0.5-2.0%, and Mg balance.
2. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite sheet according to claim 1, characterized in that: It includes the following steps: (1) mixing the components contained in the first aluminum alloy layer and performing a first smelting to obtain a first aluminum alloy; mixing the components contained in the second aluminum alloy layer and performing a second smelting to obtain a second aluminum alloy; and mixing the components contained in the magnesium alloy layer under a protective atmosphere and performing a third smelting to obtain a magnesium alloy; (2) subjecting the first aluminum alloy to a first solid solution treatment to obtain a first aluminum alloy layer; subjecting the second aluminum alloy to a second solid solution treatment to obtain a second aluminum alloy layer; and subjecting the magnesium alloy to a third solid solution treatment to obtain a magnesium alloy layer; (3) stacking the first aluminum alloy layer, the magnesium alloy layer, and the second aluminum alloy layer in order, and then rolling and heat treating them in sequence after the stacking is completed to obtain the high-strength, toughness, and corrosion-resistant aluminum-magnesium composite plate.
3. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate according to claim 2, characterized in that: In step (1), the temperatures of the first smelting and the second smelting are independently 700-770°C, and the temperature of the third smelting is 680-750°C.
4. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate according to claim 3, characterized in that: In step (2), the temperature of the first solution treatment and the second solution treatment are independently 500 to 550° C., and the time of the first solution treatment and the second solution treatment are independently 2 to 12 hours; The temperature of the third solution treatment is 450-500° C., and the time of the third solution treatment is 4-24 hours.
5. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate according to claim 4, characterized in that: In step (3), the thickness of the first aluminum alloy layer and the second aluminum alloy layer are independently 4 to 8 mm, and the thickness of the magnesium alloy layer is 6 to 10 mm.
6. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate according to claim 2 or 5, characterized in that: The number of rolling passes in step (3) is ≥ 2 times; the total rolling reduction rate is 50-85%; The rolling reduction rate of the first pass is 50-75%, and the rolling temperature of the first pass is 400-480°C; the rolling reduction rates of the remaining passes are independently 10-15%, and the rolling temperatures of the remaining passes are independently 400-490°C; the rolling temperatures of the remaining passes are ≥ the rolling temperature of the first pass.
7. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate according to claim 6, characterized in that: In step (3), the rotation speed of the upper rolling roller is 5 to 10 m / min, the rotation speed of the lower rolling roller is 3 to 8 m / min, and the asynchronous ratio of rolling is 1.2 to 1.
6.
8. The method for preparing the high-strength, toughness and corrosion-resistant aluminum-magnesium composite plate according to claim 7, characterized in that: The heat treatment temperature in step (3) is 200-300° C., and the heat treatment time is 0.5-2 h.
9. Application of the high-strength, toughness and corrosion-resistant aluminum-magnesium composite sheet material according to claim 1 in aerospace, automobile manufacturing or marine engineering.
Citation Information
Patent Citations
Composite magnesium plate ribbon of magnesium clad aluminum product and composition method
CN101049745A
Weldable metal article
CN102395693A
Aluminum-magnesium composite board and preparation method thereof
CN114292995A